REDEFINING THE ROLE OF SERVICE QUALITY AND CUSTOMER SATISFACTION IN CUSTOMER LOYALTY OF PRIVATE HIGHER EDUCATION - Nani Fitriani (Universitas Muhammadiyah Metro Lampung, 2018)
The relationship between service quality and customer satisfaction to customer loyalty during this time is considered as an established hypothesis because there are many studies that show a significant relationship between the three variables. However, a specific review of the relationship between service quality, customer satisfaction, and customer loyalty at some universities shows an interesting phenomenon. This study is a library reaseach. The purpose of the study is to fulfill the research gap that have been conducted by some researchers. The data obtained come the result of previous studies. . Based on the results of previous studies, it can be concluded that the quality of service and customer satisfaction have a significant influence on customer loyalty in the goods and services industry, in addition to the education industry. Two studies at college, Chang Li (2013) and Ham, Carrie Leugenia (2003) show that service quality and customer satisfaction did not affect customer loyalty. Thus, the established hypothesis that stated the significant influence of service quality and customer satisfaction on customer loyalty are still questionable in certain industries, especially in higher educational institutions.Keywords: Marketing, Higher Education, Service Quality, Customer Satisfaction, Customer Loyalty